CRISPR-Cas Systems Features and the Gene-Reservoir Role of Coagulase-Negative Staphylococci - Rossi, Ciro C.; Souza-Silva, Thaysa; Araújo-Alves, Amanda V.; Giambiagi-deMarval, Marcia (Frontiers in Microbiology, 2017)
The claimed role of gene reservoir of coagulase-negative staphylococci (CoNS) could be contradicted by estimates that CRISPR/Cas systems are found in the genomes of 40-50% of bacteria, as these systems interfere with plasmid uptake in staphylococci. To further correlate this role with presence of CRISPR, we analyzed, by computational methods, 122 genomes from 15 species of CoNS. Only 15% of them harbored CRISPR/Cas systems, and this proportion was much lower for S. epidermidis and S. haemolyticus, the CoNS most frequently associated with opportunistic infections in humans. These systems are of type II or III, and at least two of them are located within SCCmec, a mobile genetic element of Staphylococcus bacterial species. An analysis of the spacers of these CRISPRs, which come from exogenous origin, allowed us to track the transference of the SCCmec, which was exchanged between different strains, species and hosts. Some of the spacers are derived from plasmids described in Staphylococcus species that are different from those in which the CRISPR are found, evidencing the attempt (and failure) of plasmid transference between them. Based on the polymorphisms of the cas1 gene in CRISPRs of types II and III, we developed a multiplex-PCR suitable to screen and type CRISPR systems in CoNS. The PCR was tested in 59 S. haemolyticusstrains, of which only two contained a type III cas1. This gene was shown to be expressed in the exponential growth, stationary phase and during biofilm formation. The low abundance of CRISPRs in CoNS is in accordance with their role as gene reservoirs, but when present, their spacers sequence evidence and give an insight on the dynamics of horizontal genetic transfer among staphylococci.